IMPROVING LECTURER PERFORMANCE THROUGH LEADERSHIP STYLE, ORGANIZATIONAL CLIMATE AND WORK MOTIVATION AT BATANGHARI UNIVERSITY, JAMBI - Syekh, Saiyid; Akbar, Ali (Dinasti Publisher, 2021)
This research aims to determine Influance of leadership style, organizational climate and motivation on the performance of lecturers at Batanghari University, Jambi. The research to porpose (1) to know leadership stile, organizational climate, motivation and performance of lecturer at Batanghari University (2) to anlysis influance of leadership stile to performance of lecturer in Batanghari University (3) to analysis influance of organizational climate to performance of lecturer in Batanghari University (4) to analysis influance of motivation to performance of lecturer in Batanghari University (5) to influance of leadership style, organizational climate and motivation on the performance of lecturers at Batanghari University, Jambi. This research used survey methode with porposive sampling in 5 fakulty, with sample amounth 40 respondent. the relationship of each independent variable with the dependent variable, either individually or collectively, and makes predictions for the dependent variable on each independent variable. From the equation, it can be seen that if the leadership style can be more effective by one unit, the lecturer performance will inprove by 0.453; Likewise with the organizational climate, if the organizational climate is better by one unit, the lecturer's performance will inprove by 0.494, something that is not much different from motivation, namely if the motivation is inprove by one unit, the performance will inprovee by 0.010. This means that leadership style, organizational climate and motivation have a positive influance to lecturer performance. Therefore, it is expected that these three components (X1, X2 and X3) can be optimally priority to improved. The results of simultaneous hypothesis testing show that the value of F count is bigger than , F table. (Fcount > F table ) or sig F <0.05, this means that simultaneously, leadership style, organizational climate and motivation have significant effect on lecturer performance at University of Batanghari Jambi.